European integration: a threat to foreign investment in developing countries? - Jamuna Prasad Agarwal; Ulrich Hiemenz; Peter Nunnenkamp (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
European integration is expected to enhance the attractiveness of EL) countries for domestic and foreign investors. This has caused concerns in developing countries that foreign direct investment there may be diverted to Europe. In preparing for the Single Market, European companies have indeed become more Eurocentric, but this mainly affected their investment activities in the United States. They neglected developing countries only temporarily and largely because of macroeconomic disturbance in Latin America. Likewise, European integration has not induced US and Japanese investors to curtail their investment activities in developing countries either. Sector studies show that closer intra-EU cooperation has not stopped the worldwide globalisation of EU companies: In the EU's automobile sector, the Single Market programme has not reduced the pressure to overcome cost disadvantages through globalised production and marketing. In the chemical sector, globalisation has increased, particularly because of oligopolistic competition for the US market. In the textiles and clothing sector, suppliers have continued their globalisation efforts, as world market conditions have forced them to invest not only in Europe and North America but also in Asian developing countries. Investors are apparently aware that they cannot afford to lock themselves into Fortress Europe, thus foregoing the cost advantages of international sourcing and marketing. Central and Eastern European countries are becoming major partners in the globalisation strategies of EU companies. Investments in this region are, however, unlikely to divert investment flows away from developing countries. In particular, there are no indications that investment locations in Asia have become less attractive. This region being the world's economic growth pole, EU investors have no choice but to improve their position in the highly competitive Asian markets by exporting to, and investing in, these markets.
Keywords: 330; Direktinvestition; Multinationales Unternehmen; Europa; Osteuropa; Asien; Entwicklungsländer